Trans-resveratrol, but not other natural stilbenes occurring in food, carries the risk of drug-food interaction via inhibition of cytochrome P450 enzymes or interaction with xenosensor receptors. (January 2019) - Hyrsova, Lucie; Vanduchova, Alena; Dusek, Jan; Smutny, Tomas; Carazo, Alejandro; Maresova, Veronika; Trejtnar, Frantisek; Barta, Pavel; Anzenbacher, Pavel; Dvorak, Zdenek; Pavek, Petr
Graphical abstract: Highlights: Methoxylated stilbenes induce CYP3A4 and CYP2B6 mRNA expression. Trans -resveratrol inhibit CYP3A4 activity in micromolar concentrations. Cis -resveratrol, cis -piceatannol, oxyresveratrol and pterostilbene are weak inhibitors of CYP3A4. Only trans -resveratrol displays a risk of food-drug interactions. Abstract: Resveratrol (RSV) is a stilbene phytochemical common in food and red wine. RSV inhibits cytochrome P450 CYP3A4 activity and interacts with the pregnane X receptor (PXR), the central regulator of drug/xenobiotic metabolizing enzyme expression. In this work, we comprehensively examined the effects of 13 stilbenes ( trans - and cis -resveratrol, trans - and cis -piceatannol, oxyresveratrol, pterostilbene, pinostilbene, a, b-dihydroresveratrol, trans - and cis -trismethoxyresveratrol, trans -3, 4, 5, 4′-tetramethoxystilbene, trans -2, 4, 3′, 5′-tetramethoxystilbene, trans -4-methoxystilbene), on CYP3A4 and CYP2B6 mRNA induction, and on CYP3A4/5, CYP2C8/9/19, CYP2D6, CYP2A6, CYP2E1, CYP1A2 and CYP2B6 cytochrome P450 enzyme activities. Expression experiments in five different primary human hepatocyte preparations, reporter gene assays, and ligand binding assays with pregnane X (PXR) and constitutive androstane (CAR) receptors were performed. Inhibition of cytochrome P450 enzymes was examined in human microsomes. We found that only polymethoxylated stilbenes are prone to significantly induce CYP2B6 or CYP3A4 in primary human hepatocytes via pregnane X receptor (PXR) interaction. Natural resveratrol derivatives such as trans - and cis -RSV, oxyresveratrol, pinostilbene and pterostilbene significantly inhibit CYP3A4/5 enzymatic activities; however, only trans -RSV significantly inhibits CYP3A4/5 activity (both testosterone 6β-hydroxylation and midazolam 1´-hydroxylation) in micromolar concentrations by a non-competitive mechanism, suggesting a potential risk of food-drug interactions with CYP3A4/5 substrates.